Efektivitas Model Pembelajaran Flipped Classroom Berbasis Video Interaktif Terhadap Kemampuan Metakognitif Siswa pada Materi Bumi dan Tata Surya - Marimar intan Mustika; Aning Wida Yanti; Nailil Inayah (Universitas Garut, 2026)
In the era of 21st-century education, metacognitive ability has become a key competency that supports self- directed learning and reflective thinking, particularly in science learning. This study aims to determine the effectiveness of the flipped classroom model supported by interactive videos in enhancing students’ metacognitive abilities and learning engagement on the topic of Earth and the Solar System. The research employed a quantitative method with a pre-experimental one-group pretest–posttest design. The treatment involved implementing the flipped classroom model through two stages: a pre-class phase (independent learning through interactive videos) and an in-class phase (discussion and conceptual exploration). The study involved 31 seventh-grade students of class VII J at SMPN 25 Surabaya. The instruments consisted of an essay-based metacognitive ability test aligned with the indicators of planning, monitoring, and evaluation, as well as an observational sheet for learning engagement. The instruments were validated by experts with a Cronbach’s Alpha reliability of 0.85. Data were analyzed using a paired sample t-test and N-gain calculation. The effectiveness criteria were determined based on a significant difference between pre-test and post-test scores (p < 0.05), an N-gain value categorized as medium to high, and an improvement in learning engagement. The results showed a significant improvement from pre-test to post-test (t = 17.462; p = 0.000), with the average score increasing from 53.55 to 91.61 and an N-gain of 0.7979 (high category). Learning engagement also increased from 65% to 92% (very good category). Thus, the interactive- video-based flipped classroom model meets the effectiveness criteria and provides strong contributions to improving students’ metacognitive abilities.Keywords: Earth and the solar system, effectiveness, flipped classroom, interactive video, metacognitive skills